INTEGRASI MULTILITERASI BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN BAHASA INDONESIA: TINJAUAN FILOSOFIS DAN IMPLIKASINYA - Amelia; Heru Subrata; Hendratno; Budi Purwoko; Wahono Widodo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study addresses the gap between 21st-century multiliteracy demands and the limited integration of local wisdom in Indonesian language learning at the elementary level. It aims to formulate a conceptual model of multiliteracy-based local wisdom through a philosophical approach. A qualitative literature review was conducted on 25 scholarly sources (2020–2026), analyzed thematically across ontological, epistemological, and axiological dimensions. The findings reveal that multiliteracy expands literacy into multimodal and critical domains, while local wisdom strengthens contextual relevance and value internalization. The novelty lies in a philosophical synthesis that reconstructs Indonesian language learning as an integrative paradigm bridging global literacy and local identity. This integration leads to contextual, reflective, and transformative learning.